ANALYSIS OF IDEAS ABOUT HUMANISTIC ANTHROPOCENTRISM DURING THE WESTERN EUROPEAN EARLY RENAISSANCE - Suvonova Umida Amriddin qizi (Academia Science Repository, 2023)
Humanism is a concept expressing concerned human dignity, freedom, happiness, equal rights, creating conditions for the manifestation of all the principles of humanity. According to its, the most valuable thing in the world is a person, the whole being should serve a person and his happiness. Caring for human destiny, interests of the people, people of the country is the main issue of humanism. In this article, the reasons for the emergence of humanist ideas in Western Europe and its essence are philosophically analyzed.